Non-audit Fees and Auditor Independence: Supply Side Considerations Initial audit fee discounting and the supply of NAS - Prasad, Pranil (IJRDO - Journal of Business Management, 2016)
The joint provision of audit and non-audit services remains a contentious issue for the regulators, legislators and the auditing profession to date. In the past two decades, audit research has examined whether the joint provision of audit and non-audit services impairs auditor independence. However, empirical evidence on non-audit services and auditor independence has remained mixed and inconclusive. This paper seeks to contribute to debate on the joint supply of audit and non-audit services by empirically investigating the supply side of the market for non-audit services. In particular, a model for the supply side of the market for non-audit services is developed and empirically tested. A supply side focus can be potentially informative because the reason why auditors supply non-audit services to their audit clients can have important implications for the independence of the auditor. An ordinary least squares regression model is used to model the supply side of the market for non-audit services. In addition, a panel dataset is used. The data relates to a sample of the companies listed on the Australian Securities Exchange from the year 2000 to 2010. The results of this study indicate that auditors supply non-audit services to audit clients for efficiency rather than opportunistic reasons. This study provides regulators and legislators in Australia with important insights into the supply of non-audit services by incumbent auditors to their audit clients.